2003
DOI: 10.2337/diacare.26.7.1993
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Diabetes in the Manitoba-Registered First Nation Population

Abstract: OBJECTIVE -This study provides an overview of the epidemiology of diabetes in the Manitoba First Nation population. RESEARCH DESIGN AND METHODS -The study uses data derived from the population-based Manitoba Diabetes Database to compare the demographic and geographic patterns of diabetes in the Manitoba First Nation population to the non-First Nation population.RESULTS -Although the prevalence of diabetes rose steadily in both the First Nation and the non-First Nation populations between 1989 and 1998, the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
53
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 12 publications
(8 reference statements)
5
53
1
Order By: Relevance
“…These observations suggest fundamental differences between populations in the mechanisms underlying diabetes; this has widespread implications that are probably also relevant to other indigenous and developing populations. 1 Our findings are consistent with reports that used similar methods 8,9 to show higher prevalence of diabetes among First Nations people than among non-First Nations people in neighbouring provinces. This difference appears to be at least partly because of higher rates of overweight and obesity among First Nations people.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations suggest fundamental differences between populations in the mechanisms underlying diabetes; this has widespread implications that are probably also relevant to other indigenous and developing populations. 1 Our findings are consistent with reports that used similar methods 8,9 to show higher prevalence of diabetes among First Nations people than among non-First Nations people in neighbouring provinces. This difference appears to be at least partly because of higher rates of overweight and obesity among First Nations people.…”
Section: Discussionsupporting
confidence: 89%
“…5,6 Although an increased prevalence of diabetes among First Nations people has also been documented in other Canadian provinces, 3 only recently have consistent diabetes case definitions applied to health care system administrative databases been used to compare differences between large populations of First Nations and non-First Nations people. [7][8][9] We sought to describe the epidemiology of diabetes in Saskatchewan from 1980 to 2005. We reasoned that finding ethnicity-based differences in trends and patterns of type 2 diabetes over the longest period reported for a Canadian jurisdiction would help to clarify the underlying mechanisms behind known disparities and translate into more effective diabetes prevention and management initiatives.…”
mentioning
confidence: 99%
“…These findings are consistent with population-based diabetes reports showing higher incidence and prevalence of diabetes among First Nations people than among non-First Nations people. 24,29,30 Dyck and associates 24 reported that the incidence and prevalence of diabetes were more than 4 times higher among First Nations women than among nonFirst Nations women, and more than 2.5 times higher among First Nations men than among nonFirst Nations men. The reasons that have been attributed to these differences include genetic susceptibility, [31][32][33][34] dietary acculturation, 34,35 adoption of sedentary lifestyle 34,36 and increasing prevalence of obesity and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These observed prevalence rates may underestimate the current prevalence of the syndrome in Native Canadian populations, as over the past decade the prevalence of obesity and diabetes in Aboriginal population has been steadily increasing. 9,54 Given the diverse nature of these populations, careful consideration should be given to developing culturally appropriate community-based prevention strategies aimed at reducing the frequency of this syndrome. 55,56 …”
Section: Discussionmentioning
confidence: 99%